Junctures in women's leadership : the arts - Brodsky, Judith K.; Olin, Ferris (New Brunswick : Rutgers University Press, 2018)
"In this third volume of the series Junctures: Case Studies in Women's Leadership, Judith K. Brodsky and Ferris Olin profile female leaders in music, theater, dance, and visual art. The diverse women included in Junctures in Women's Leadership: The Arts have made their mark by serving as executives or founders of art organizations, by working as activists to support the arts, or by challenging stereotypes about women in the arts. The contributors explore several important themes, such as the role of feminist leadership in changing cultural values regarding inclusivity and gender parity, as well as the feminization of the arts and the power of the arts as cultural institutions"--
Bertha Honoré Palmer -- Louise Rosenfield Noun -- Samella Sanders Lewis -- Julia Miles -- Míriam Colón -- Jaune Quick-to-See Smith -- Bernice Steinbaum -- Anne d'Harnoncourt -- Martha Wilson -- Jawole Willa Jo Zollar -- Kim Berman -- Gilane Tawadros -- Veomanee Douangdala and Joanne Smith.
Includes bibliographical references and index.
Print version record.
JSTOR
Keywords: Leadership in women; Women executives; Women in art; Leadership chez la femme; Femmes dans l'art.; ART -- History -- Contemporary (1945- ); SOCIAL SCIENCE -- Women's Studies; BUSINESS & ECONOMICS -- Leadership; PERFORMING ARTS -- Business Aspects; SOCIAL SCIENCE -- Feminism & Feminist Theory; ART -- Individual Artists -- Essays; ART -- General; Leadership in women; Women executives; Women in art